Disease Centered Around Calcified Taenia solium Granuloma. Issue 1 (January 2017) - Nash, Theodore E.; Bustos, Javier A.; Garcia, Hector H.; ,
Abstract : Taenia solium (the pork tapeworm) is present in most developing countries, where it is a frequent cause of seizures and other neurological disease. Parasitic larvae invade the human brain, establish, and eventually resolve, leaving a calcified scar. While these lesions are common in endemic regions, and most of these are clinically silent, a proportion of individuals with calcified cysticerci develop seizures from these lesions, and 30–65% of these cases are associated with perilesional edema (PE), likely due to host inflammation. This manuscript summarizes the importance, characteristics, natural history, and potential prevention and treatments of symptomatic calcified neurocysticercosis (NCC). Trends: Calcified brain cysticercosis lesions can be found in a sizable (10–20%) proportion of people living in endemic regions. Calcified NCC is strongly associated with epilepsy: lesions are more prevalent in symptomatic compared to asymptomatic participants, and seizure semiology is frequently concordant with the localization of the calcified lesion. Seizures in individuals with calcified disease are frequently associated with perilesional brain edema around one or more calcified lesions. Gliosis surrounding calcified lesions seems to be associated with refractory epilepsy. Calcified NCC has been associated with hippocampal sclerosis, both for lesions in the temporal lobe as well as for distant lesions.